Sustainable Pavement Development Through Plastic Bottle Waste Utilization: A Performance and Cost Analysis: english - Pangestika, Safety Husna; Ikhsani, Muhammad Azmy; Ayu, Artanti Kusuma (Teknik Lingkungan Universitas Islam Indonesia, 2026)
Indonesia is ranked among the top eight countries contributing the largest amount of plastic waste globally, producing approximately 3.4 million tons annually. One potential strategy to address this issue is the utilization of plastic waste in asphalt mixtures, which can enhance road infrastructure performance. This study employs mineral water bottle waste made of Polyethylene Terephthalate (PET), which is abundantly available but remains underutilized. In this research, PET was substituted into AC-WC asphalt mixtures using the wet mixing method with variations of 0%, 2%, 5%, 6%, and 8%. Each variation was tested using the Marshall method at the optimum asphalt content (OAC) to evaluate the mixture characteristics. Unlike previous studies that mainly emphasized technical aspects, this research also considers cost efficiency. The findings indicate that the optimum level was achieved at 5% PET, which increased the mixture strength by up to 28.44% compared to conventional asphalt, while reducing construction costs by as much as 2.02%. These results demonstrate that incorporating mineral water bottle waste not only improves pavement strength but also offers economic benefits and supports efforts to reduce plastic waste